Accounting for Genetic Differences Among Unknown Parents in Bubalus bubalis: A Case Study From the Italian Mediterranean Buffalo - Gómez, Mayra; Rossi, Dario; Cimmino, Roberta; Zullo, Gianluigi; Gombia, Yuri; Altieri, Damiano; Di Palo, Rossella; Biffani, Stefano (Frontiers in Genetics, 2021)
The use of genetic evaluations in the Water Buffalo by means of a BLUP animal model has been increasing over the last two-decades across several countries. However, natural mating is still a common reproductive strategy and it can increase the proportion of missing pedigree information. The inclusion of genetic groups in variance component (VC) and breeding value (EBV) estimation is a possible solution. The aim of this study was to evaluate different genetic grouping strategies and their effects on VC and EBV for composite (n=5) and linear (n=10) type traits in the Italian Mediterranean Buffalo population. Type traits data from 7,714 buffalo cows plus a pedigree file including 18,831 individuals were provided by the Italian National Association of Buffalo Breeders. VCs and EBVs were estimated for each trait fitting a single-trait animal model and using the official DNA-verified pedigree. Successively, EBVs were re-estimated using modified pedigrees with two different proportion of missing genealogies (30 or 60 % of buffalo with records), and two different grouping strategies, year of birth (Y30/Y60) or genetic clustering (GC30, GC60). The different set of VCs, estimated EBVs and their standard errors were compared with the results obtained using the original pedigree. Results were also compared in terms of efficiency of selection. Differences among VCs varied according to the trait and the scenario considered. The largest effect was observed for two traits, udder teat and body depth in the scenario GC60, whose heritability decreased by -0.07 and increased by +0.04 respectively. Considering buffalo cows with record, the average correlation across traits between official EBVs and EBVs from different scenarios was 0.91, 0.88, 0.84 and 0.79 for Y30, CG30, Y60 and CG60, respectively. In bulls the correlations between EBVs ranged from 0.90 for fore udder attachment and udder depth to 0.96 for stature and body length in the GC30 scenario and from 0.75 for udder depth to 0.90 for stature in the GC60 scenario. When a variable proportion of missing pedigree is present using the appropriate strategy to define genetic groups and including them in variance component and breeding value estimation is a worth-while and low-demanding solution.